2021
DOI: 10.15869/itobiad.804663
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Analysis on International Migration as a Determinant of Regional Development in Turkey

Abstract: Bu makale, en az iki hakem tarafından incelenmiş ve intihal içermediği teyit edilmiştir. / This article has been reviewed by at least two referees and confirmed to include no plagiarism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…Many studies examine the relationship between international capital and population mobility with economic growth or development [6,15,16,[29][30][31][32]. While empirical studies mostly look into the effects of international capital and population mobility on the country's economy, few other studies measure their effects on the economic growth or socioeconomic development level at the regional or urban level [16,33]. Studies examining international capital mobility investigate the short or long-term effects of foreign investments on countries' or regions' economies.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies examine the relationship between international capital and population mobility with economic growth or development [6,15,16,[29][30][31][32]. While empirical studies mostly look into the effects of international capital and population mobility on the country's economy, few other studies measure their effects on the economic growth or socioeconomic development level at the regional or urban level [16,33]. Studies examining international capital mobility investigate the short or long-term effects of foreign investments on countries' or regions' economies.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They found that in Turkey, there is a significant and negative relationship between economic growth and migration. Demirtaş et al [16] investigated the effect of international migration on regional development of Turkey by using panel data analysis. The main result of the study is that international migration inflows have a positive impact on regional development.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from physical capital, another critical factor for development is human capital. As it is known, human capital is an essential factor in endogenous growth models, as it is an essential input in the field of research and development, which forms the basis for technological development, such as producing new products (Demirtaş et al, 2021). Industrial and technological developments are based on social capital.…”
Section: Literaturementioning
confidence: 99%
“…International migration, also referred to as external migration, is defined as settling in another country temporarily and permanently (Şantaş, 2019). The connection of international migration with economic growth has been a widely discussed topic in both national (Demirtaş et al, 2021;İşcan and Demirel, 2021;Meçik and Koyuncu, 2020;Engin and Konuk, 2020;Altunç et al, 2017;Kaypak and Bimay, 2016) and international (Tanrikulu, 2020;Murata, 2018;Brunow et al, 2015;Chen and Fang, 2013;Chen, 2006) literature. Internal migration, on the other hand, is defined as migration that occurs within the borders of the country.…”
Section: Introductionmentioning
confidence: 99%